Invaluable values: an expectancy-value theory analysis of youths' academic motivations and intentions. Issue 5 (3rd May 2016) - Ball, Christopher; Huang, Kuo-Ting; Cotten, Shelia R.; Rikard, R.V.; Coleman, LaToya O.
ABSTRACT: While Science, Technology, Engineering, and Math (STEM) fields have increased in importance over the past decade, minorities have remained traditionally underrepresented in these fields. In this study we seek to better understand some of the factors that might contribute to or potentially mitigate early STEM pipeline leaks, specifically, high school graduation and college entrance leaks. Student interest formed in the early school years has an impact on future course selections and persistence in school. These choices can have long-term repercussions on the future career options and the financial security of students. We apply expectancy-value theory (EVT) in order to examine the factors that may influence students' motivations and intentions to complete high school and attend college. Specifically, we investigate if EVT can help to explain change in students' academic intentions and motivations after a computing intervention. We hypothesize that changes in students' expectancies for success and subjective task values will be positively associated with changes in students' intentions and motivations to persist in academia. Data were gathered from a sample of elementary students within an urban, high poverty, and predominately minority school district located in the southeastern USA. Changes in students' expectancies for success and subjective task values over the course of the intervention played an important role in students' academic motivations and intentions to both finish high school and attend college. These findings demonstrate that EVT is useful in explaining general academic motivations in young children, which could potentially increase the structural integrity of the STEM pipeline.